Analysis of the role of retrotransposition in gene evolution in vertebrates - Ivanga Mahine; Morais David; Yu Zhan; Harrison Paul M (BMC Bioinformatics, 2007)
Abstract Background The dynamics of gene evolution are influenced by several genomic processes. One such process is retrotransposition, where an mRNA transcript is reverse-transcribed and reintegrated into the genomic DNA. Results We have surveyed eight vertebrate genomes (human, chimp, dog, cow, rat, mouse, chicken and the puffer-fish T. nigriviridis), for putatively retrotransposed copies of genes. To gain a complete picture of the role of retrotransposition, a robust strategy to identify putative retrogenes (PRs) was derived, in tandem with an adaptation of previous procedures to annotate processed pseudogenes, also called retropseudogenes (RψGs). Mammalian genomes are estimated to contain 400–800 PRs (corresponding to ~3% of genes), with fewer PRs and RψGs in the non-mammalian vertebrates. Focussing on human and mouse, we aged the PRs, analysed for evidence of transcription and selection pressures, and assigned functional categories. The PRs have significantly less transcription evidence mappable to them, are significantly less likely to arise from alternatively-spliced genes, and are statistically overrepresented for ribosomal-protein genes, when compared to the proteome in general. We find evidence for spurts of gene retrotransposition in human and mouse, since the lineage of either species split from the dog lineage, with >200 PRs formed in mouse since its divergence from rat. To examine for selection, we calculated: (i) Ka/Ks values (ratios of non-synonymous and synonymous substitutions in codons), and (ii) the significance of conservation of reading frames in PRs. We found >50 PRs in both human and mouse formed since divergence from dog, that are under pressure to maintain the integrity of their coding sequences. For different subsets of PRs formed at different stages of mammalian evolution, we find some evidence for non-neutral evolution, despite significantly less expression evidence for these sequences. Conclusion These results indicate that retrotranspositions are a significant source of novel coding sequences in mammalian gene evolution.